2002
DOI: 10.1097/00007890-200209270-00005
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of T cell depletion in murine renal ischemia-reperfusion injury.

Abstract: These data demonstrate that T cell depletion can improve the course of experimental renal IRI. However, more aggressive T cell depletion strategies were required compared with that needed to prevent experimental allograft rejection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
97
1
3

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 125 publications
(104 citation statements)
references
References 15 publications
3
97
1
3
Order By: Relevance
“…Aberrant CALCA gene methylation arises universally and de novo during leukemic transformation in hematopoietic progenitors developing in the lymphoid pathway (B or T cell lineage) (51). Since it has been shown that CD4+ T cells may play a pathogenic role in ischemic acute renal failure (52,53) as well as in acute rejection, we believed that aberrant hypermethylation of the CALCA gene which seems to be involved in the lymphoid pathway may be a biomarker of the two main causes of acute kidney injury in transplantation; mainly acute rejection and acute tubular necrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Aberrant CALCA gene methylation arises universally and de novo during leukemic transformation in hematopoietic progenitors developing in the lymphoid pathway (B or T cell lineage) (51). Since it has been shown that CD4+ T cells may play a pathogenic role in ischemic acute renal failure (52,53) as well as in acute rejection, we believed that aberrant hypermethylation of the CALCA gene which seems to be involved in the lymphoid pathway may be a biomarker of the two main causes of acute kidney injury in transplantation; mainly acute rejection and acute tubular necrosis.…”
Section: Discussionmentioning
confidence: 99%
“…17,18 A role for CD8 þ T cells in ischemia-reperfusion injury of the kidney has also been demonstrated. 19,20 Ayala and colleagues showed that blockade of Fas/FasL interactions will ablate CLP-induced injury. 21,22 CD8 þ T and NK cells utilize the Fas/FasL pathway to induce cellular lysis and injury in a variety of scenarios.…”
Section: Discussionmentioning
confidence: 99%
“…Mice deficient in both CD4 + and CD8 + T cells had reduced functional and structural abnormalities after IRI [37]. Athymic nu/nu mice were also protected from renal IRI, and adoptive transfer of wild type T cells abolished these effects both in clamp and whole body IRI models [38,39]. Interestingly, neither neutrophil nor macrophage infiltration was changed in this model, suggesting a neutrophil/macrophage-independent effect of T cells in IRI.…”
mentioning
confidence: 88%
“…This combination depleted T cells but did not protect renal function after ischemia. However, the addition of a third antibody (30.H12) that targets Th1.2 antigen decreased T cells further, in particular the CD4 + subset, and led to renal protection [39]. In the late phase (6 weeks) of severe renal IRI, there was a marked infiltration of CD4 + T cells throughout the injured kidney, which may promote the development of chronic renal disease [41].…”
Section: Different Roles Of T Cell Subsets In Irimentioning
confidence: 99%